Descriptions of Cranfield Aircraft Group design projects (1979-96) - Fielding, J. P. (Cranfield University, 1996)
This report is a compilation of reprints of papers and articles describing the aircraft design group projects for the period between 1979 to 1996. In Crdeld projects, each student takes responsibility for part of the design of a project aircraft, which is used as a design case study for the whole group of students of the course. This teamwork exercise, with specified individual tasks, is organised on the lines of a project as carried out in industry. It is undertaken over eight months, in parallel with the lectures and individual research studies. It is assisted by displays of aircraft components and manufacturing processes, and field visits are made to aircraft manufacturers and operators. The nature of the course and the future occupations of the students, give guidance to the choice of subject aircraft. The aim is to ensure industrial relevance, but also to include a significant research element in each project. The size of the course usually precludes the design of light aircraft. It is usual to alternate between civil and military aircraft, and each project has a unique configuration.